Saroyan's Filipinos: Undoing Invisibility and Silence in Subaltern Spaces - Aguilera Linde, Mauricio D. (Archīum Ateneo, 2024)
Before John Fante’s stories about Filipinos and Carlos Bulosan’s autobiography were published, William Saroyan’s depiction of Filipino migrant workers provided one of the earliest representations of a minority doomed to invisibility and silence during the 1930s and 1940s. This article offers a careful reading of the Filipino’s presence in his fiction through an analysis of the narratorial techniques deployed and the symbolism of the characters in two of his stories, “Our Little Brown Brothers the Filipinos” (1936) and “1924 Cadillac for Sale” (1938). In the first, by resorting to the tradition of the tall tale in a boxing story, the author disavows the raconteur’s ideology of racism and the hegemonic belief in the Great White Hope. Ramon’s victory signals the suspension of the alleged inferiority of the “brown savages” and becomes the stand-in justification for the long-overdue vindication of his people. Simultaneously, by allowing the Filipino farmhand to fix the jalopy in the second title, Saroyan manages to resurrect the pastoral ideal of America, thereby reviving the belief that marginalized immigrants, and not machines, can still be the driving force of the nation weathering an economic crisis.